1999
DOI: 10.1097/00132586-199904000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Budesonide and Oral Dexamethasone for Treatment of Croup: A Randomized Controlled Trial

Abstract: Context.-The effectiveness of glucocorticoids for patients with croup is well established but it remains uncertain which glucocorticoid regimen is most effective.Objective.-To determine the effectiveness of 3 glucocorticoid regimens in patients with croup.Design.-Randomized controlled trial with parallel design. Setting.-Emergency departments of 2 Canadian pediatric tertiary care hospitals.Participants.-Children with a clinical syndrome consistent with croup, aged 3 months to 5 years, with a croup score of 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 0 publications
2
37
1
4
Order By: Relevance
“…There are several versions of it; the original scale takes into account the following symptoms: stridor (0-2 points), chest wall retraction (0-3), air entry (0-2 points), cyanosis when breathing room air (0 -5 points), consciousness (0-5 points) [10].Positive results of the inhaled corticosteroid are also described in patients with mild / moderately symptomatic ASLT. It was shown that appointment of a suspension of budesonide for patients with Westley index from 2 to 7 points led to a rapid (within the first 4 hours) and clinically significant improvement (from 4 to 1 point) [11]. Satisfactory response to therapy was observed after 4 hours in 70% of patients treated with inhaled corticosteroid, and only in 37% of the placebo group patients [11].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several versions of it; the original scale takes into account the following symptoms: stridor (0-2 points), chest wall retraction (0-3), air entry (0-2 points), cyanosis when breathing room air (0 -5 points), consciousness (0-5 points) [10].Positive results of the inhaled corticosteroid are also described in patients with mild / moderately symptomatic ASLT. It was shown that appointment of a suspension of budesonide for patients with Westley index from 2 to 7 points led to a rapid (within the first 4 hours) and clinically significant improvement (from 4 to 1 point) [11]. Satisfactory response to therapy was observed after 4 hours in 70% of patients treated with inhaled corticosteroid, and only in 37% of the placebo group patients [11].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%
“…It was shown that appointment of a suspension of budesonide for patients with Westley index from 2 to 7 points led to a rapid (within the first 4 hours) and clinically significant improvement (from 4 to 1 point) [11]. Satisfactory response to therapy was observed after 4 hours in 70% of patients treated with inhaled corticosteroid, and only in 37% of the placebo group patients [11].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%
“…Through their research, significant contributions have been made to the evidence base for the treatment of croup and bronchiolitis, 2-14 the use of radiology for ankle and knee injuries in children, 15,16 the use of computed tomography in children with minor head injury, [17][18][19] and the implementation of spacers and metered-dose inhalers in the ED. 20 The quality of the research is reflected in substantial funding from major provincial and national funders, as well as publications in high-impact journals such as the New England Journal of Medicine, 2,4 the Journal of the American Medical Association, 5,21 and the British Medical Journal. 7 The research conducted by PERC members has been principally driven by single investigators or centers and funded on a per-project basis from various sources.…”
mentioning
confidence: 99%
“…Research of Canada (PERC) members who have conducted a substantial number of randomized controlled trials (RCTs) to evaluate the efficacy of different treatments for croup [1][2][3][4][5] and most importantly to solidly demonstrate the benefit of corticosteroids and the relative efficacy of different corticosteroids in croup of varying severity. 2,4,5 The nature of the RCTs demonstrates the maturity and successes of this research team; earlier studies involved single centers with relatively small samples (e.g., 54 patients 1 and 50 patients 5 ) compared with a more recent trial involving four centers and 720 children.…”
mentioning
confidence: 99%
See 1 more Smart Citation